Предмет: Математика,
автор: Lunaki
229 пожалуйста , спасибки
Приложения:
![](https://files.topotvet.com/i/ab9/ab9c3d7561d52150c2535c9528682822.jpg)
Ответы
Автор ответа:
1
a) x(-1 - 2 - 3) + 6x = -6x + 6x = 0 - доказано
б) a(-5 + 4 - 3 + 2) = a * (-8 + 6) = -2a - доказано
Lunaki:
Спасибо вам огромное
Автор ответа:
1
-х -2х -3х +6х=-6х+6х=0
-5а+4а-3а+2а=-2а
-5а+4а-3а+2а=-2а
Похожие вопросы
Предмет: Математика,
автор: lizalogika
Предмет: Химия,
автор: kolbinevgeniy1501
Предмет: Немецкий язык,
автор: point56
Предмет: Математика,
автор: ksksksksksksksksks
Предмет: Математика,
автор: алишка2201